Moringa Genus: A Review of Phytochemistry and Pharmacology - Abd Rani, Nur Zahirah; Husain, Khairana; Kumolosasi, Endang (Frontiers in Pharmacology, 2018)
Moringa is a genus of medicinal plants that has been used traditionally to cure wounds and various diseases such as colds, and diabetes. In addition, the genus is also consumed as a source of nutrients and widely used for purifying water. The genus consists of 13 species that have been widely cultivated throughout Asia and Africa for their multiple uses. The purpose of this review is to provide updated and categorized information on the traditional uses, phytochemistry, biological activities, and toxicological research of Moringa species in order to explore their therapeutic potential and evaluate future research opportunities. The literature reviewed for this paper was obtained from PubMed, ScienceDirect, and Google Scholar journal papers published from 1983 to March 2017. Moringa species are well known for their antioxidant, anti-inflammatory, anticancer, and antihyperglycemic activities. Most of their biological activity is caused by their high content of flavonoids, glucosides, and glucosinolates. By documenting the traditional uses and biological activities of Moringa species, we hope to support new research on these plants, especially on those species whose biological properties have not been studied to date.